A Bibliometric Analysis of Health and Medical Journals: Issues in Medical Scholarly Communication in Africa. Issue 2 (2nd April 2016) - Ezema, Ifeanyi J.; Onyancha, Omwoyo Bosire
ABSTRACT: The study was conducted to examine the scholarly impact of health and medical journals in Africa. A descriptive informetric research approach was used to analyze 134 health and medical journals hosted in the African Journal Online (AJOL) database. Harzing's Publish or Perish (PoP) software was used to extract publication and citation indicators of the journals. These indicators include number of citations, number of paper publications, cites per year, cites per paper, and the h-index of the journals. The performance of the journals was equally examined in other major databases like Thomson Reuters and Scopus. Findings reveal that only 20 African countries contributed health and medical journals to the AJOL database, with Nigeria and South Africa producing nearly 70% of the journals. A ranked list of 29 journals was developed, with South African Medical Journal and African Health Sciences ranking highest in the list, respectively. Only 14 of the journals were found in Thompson Reuters, while Scopus indexes only 38.8% of the journals. These findings challenge the criteria Thompson Reuters and Scopus use in the selection of journals for their databases.